High-Performance Carbon Nanotube-Based Transient Complementary Electronics - Fan Xia; Xia, Tian; Li Xiang; Fang Liu; Jia, Weijie; Liang, Xuelei; Hu, Youfan (ACS Applied Materials & Interfaces, 2022)
Transient electronics is an emerging class of electronic devices that can physically degrade or disintegrate after a stable period of service, showing a vast prospect in applications of “green” consumer electronics, hardware-secure devices, medical implants, etc. Complementary metal-oxide–semiconductor (CMOS) technology is dominant in integrated circuit design for its advantages of low static power consumption, high noise immunity, and simple design layout, which also work and are highly preferred for transient electronics. However, the performance of complementary transient electronics is severely restricted by the confined selection of transient materials and compatible fabrication strategies. Here, we report the realization of high-performance transient complementary electronics based on carbon nanotube thin films via a reliable electrostatic doping method. Under a low operating voltage of 2 V, on a 1.5 μm-thick water-soluble substrate made of poly(vinyl alcohol), the width-normalized on-state currents of the p-type and n-type transient thin-film transistors (TFTs) reach 4.5 and 4.7 μA/μm, and the width-normalized transconductances reach 2.8 and 3.7 μS/μm, respectively. Meanwhile, these TFTs show small subthreshold swings no more than 108 mV/dec and current on/off ratios above 106 with good uniformity. Transient CMOS inverters, as basic circuit components, are demonstrated with a voltage gain of 24 and a high noise immunity of 67.4%. Finally, both the degradation of the active components and the disintegration of the functional system are continuously monitored with nontraceable remains after 10 and 5 h, respectively.